Pengaruh Kegiatan Rohani Terhadap Pertumbuhan Spiritual Siswa SMP Kristen Kalam Kudus Yogyakarta - ramses simanjuntak; Filien Krisnasari; Jubliana Netha Ratu Pa (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2022)
Junior High School students are classified as teenagers. Adolescents are the ages of children reaching adulthood who are looking for their own identity, so it is called puberty (sexual maturity). These teenagers tend to imitate other people, for example, parents, idols, or artists. Teenagers are also quickly affected from the positive and negative aspects. Junior high school students also have spiritual activities to support their faith growth. Spiritual activities are activities that support a person to increase spiritual growth. Spiritual activities can be done in churches and schools. In Christian schools, there are many spiritual programs and activities, including morning prayer, joint worship, Easter and Christmas services. Students are taught to increase the growth of their spiritual faith in God and become children who fear God and can have a positive impact on other children. In the house, parents must also have a role in the spiritual growth of their children, spiritual activities must be carried out, especially in the family, the family becomes the basis where the child has the knowledge or knowledge to know what is good and what is not. Spiritual activities should be emphasized in early childhood. But many Christian families do not apply spiritual activities to their children, because of the busyness of each parent. The author is worried about the future of students who don't get a good spiritual life, this is the responsibility of parents because parents are God's representatives, in the Bible Deuteronomy 6: 4-9 the duties of parents must be carried out because it is the basis of the child to learn various things, including faith in God.